2019
DOI: 10.1029/2019ja026816
|View full text |Cite
|
Sign up to set email alerts
|

SuperDARN Observations During Geomagnetic Storms, Geomagnetically Active Times, and Enhanced Solar Wind Driving

Abstract: The Super Dual Auroral Radar Network (SuperDARN) was built to study ionospheric convection at Earth and has in recent years been expanded to lower latitudes to observe ionospheric flows over a larger latitude range. This enables us to study extreme space weather events, such as geomagnetic storms, which are a global phenomenon, on a large scale (from the pole to magnetic latitudes of 40°). We study the backscatter observations from the SuperDARN radars during all geomagnetic storm phases from the most recent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(105 citation statements)
references
References 62 publications
3
102
0
Order By: Relevance
“…A similar analysis was presented in Hutchinson, Wright, and Milan (2011) for Solar Cycle 23 but concluded that storm main phase duration increases with intensity to a point, but then the relationship reverses for storms more intense than a peak SYM-H index disturbance of −150 nT. Recently, Walach and Grocott (2019) analysed the SYM-H index between 2010 and 2016 in a similar way to Hutchinson, Wright, and Milan (2011) but concluded that there was no clear ordering of intensity by storm duration. Conversely, Vennerstrom et al (2016) used the aa index to demonstrate an increase in average storm duration across five peak intensity levels.…”
Section: Introductionmentioning
confidence: 74%
“…A similar analysis was presented in Hutchinson, Wright, and Milan (2011) for Solar Cycle 23 but concluded that storm main phase duration increases with intensity to a point, but then the relationship reverses for storms more intense than a peak SYM-H index disturbance of −150 nT. Recently, Walach and Grocott (2019) analysed the SYM-H index between 2010 and 2016 in a similar way to Hutchinson, Wright, and Milan (2011) but concluded that there was no clear ordering of intensity by storm duration. Conversely, Vennerstrom et al (2016) used the aa index to demonstrate an increase in average storm duration across five peak intensity levels.…”
Section: Introductionmentioning
confidence: 74%
“…To extract storm time periods for analysis, storms were identified using the algorithm described by Walach and Grocott (2019). The reader is referred to Walach and Grocott (2019) for full details, and we summarize the key aspects here. The algorithm identifies storms from variations in the Sym‐H index, and a typical Sym‐H index trace is shown in Figure 1.…”
Section: Estimating the Ring Current Energy Content During Stormsmentioning
confidence: 99%
“…The initial phase is present for most storms and is characterized by an enhancement in the Sym-H index driven by enhancements in the magnetopause currents. The initial phase typically lasts ∼20 h (Walach & Grocott, 2019). The main phase is identified from a sharp and rapid negative excursion in the Sym-H index, driven by significant energization of the ring current, and has a typical duration of ∼8 h (Walach & Grocott, 2019).…”
Section: Storm Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent events can be analysed with the help of the potential modelling based on radar data of higher time resolution such as provided by present SuperDARN (Nishitani et al 2019). The SuperDARN also extends its facilities in order to be able to study lower-latitude phenomena and large magnetospheric disturbances (Baker et al 2007;Clausen et al 2012;Walach and Grocott 2019). It is anticipated that an extended spatial range of SuperDARN radars may support further studies on topics considered in this paper (Odzimek 2019b).…”
Section: Discussionmentioning
confidence: 96%